STRATEGI POLDA KALIMANTAN BARAT DALAM MENGAMANKAN PENYELENGGARAAN PILKADA KALIMANTAN BARAT TAHUN 2012 DIHUBUNGKAN DENGAN PENYELENGGARAAN PILKADA KABUPATEN/KOTA DI KALIMANTAN BARAT TAHUN 2013. - DAVID M. SIAHAAN, SE. A.21211053, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2014)
ABSTRACT This thesis discusses the problems in West Kalimantan regional police strategy in securing the organization of local elections in West Kalimantan in 2012 associated with the implementation of election districts / cities in West Kalimantan in 2013 .. From the research using sociological research methods juridical law is concluded, that: In order to safeguard the organization of the elections in 2012 the election of Governor / Deputy Governor and Singkawang elections and securing the implementation of election 2013 District / town in 4 (four) regions, namely the city of Pontianak, Kubu district highways, district and Sanggau Pontianak, Kubu district highways, district and Sanggau Pontianak, the police conduct internal organization that is organizing the parts and Police operational units into a united force and well coordinated organization should also be done externally, namely the Government of Regency / City KPU District / Town, District election Supervisory Committee / City, campaign organizers and community potential in an integrated and coordinated systematically according to the task, roles and functions and responsibilities of each in order to secure the election campaign can be run safely and orderly. Election security system in 2013 in 4 (four) districts / cities, in terms of 7 (seven) forms of implementation can be grouped into three (3) security systems are: System security election campaign with a rally form, face to face, and the meeting limited, security system with a form of election campaign broadcasting through radio and or television, and the system securing the election campaign with a form of dissemination through print and electronic media as well as the installation of props in a public place. The activities were carried out after both the internal organization of the police and together with the relevant agencies, institutions and potential public elections, among others: realize campaigning activities conducive situation, the activity of making an agreement among the political parties contesting the election, the combined strength building activities, deterrence activities (pre-emptive), prevention (preventive) and enforcement (repression). ABSTRAK Tesis ini membahas masalah strategi polda kalimantan barat dalam mengamankan penyelenggaraan pilkada kalimantan barat tahun 2012 dihubungkan dengan penyelenggaraan pilkada kabupaten/kota di kalimantan barat tahun 2013.. Dari hasil penelitian menggunakan metode penelitian hukum yuridis sosiologis diperoleh kesimpulan, bahwa : Dalam rangka pengamanan penyelenggaraan Pilkada tahun 2012 yaitu pilkad Gubernur/wakil Gubernur dan Pilkada Singkawang dan pengamanan penyelenggaraan pilkada 2013 Kabupaten/kota di 4 (empat) wilayah yaitu Kota Pontianak, Kabupaten Kubu raya, Kabupaten Pontianak dan Kabupaten Sanggau, Polri melakukan pengorganisasian secara intern yaitu pengorganisasian bagian-bagian dan satuan-satuan operasional Polri menjadi suatu kekuatan yang utuh dan terkoordinir dengan baik perlu juga dilakukan pengorganisasian secara ekstern yaitu dengan Pemerintahan Kabupaten/Kota,KPU Kabupaten/Kota,Panwaslu Kabupaten/Kota,panitia penyelenggara kampanye dan potensi masyarakat secara terpadu dan terkoordinir secara sistimatis sesuai tugas, peran dan fungsi serta tanggung jawabnya masing-masing dalam rangka pengamanan kampanye Pilkada dapat berjalan aman dan tertib. Sistem pengamanan Pilkada tahun 2013 di 4 (empat) Kabupaten/kota, ditinjau dari 7 ( tujuh ) bentuk pelaksanaan dapat dikelompokkan menjadi 3 ( tiga ) sistem pengamanan yaitu : Sistem pengamanan kampanye Pilkada dengan bentuk rapat umum, tatap muka, dan pertemuan terbatas, sistem pengamanan kampanye Pilkada dengan bentuk penyiaran melalui radio dan atau televisi, dan sistem pengamanan kampanye Pilkada dengan bentuk penyebaran melalui media cetak dan media elektronik serta pemasangan alat peraga di tempat umum. Adapun kegiatan yang dilaksanakan setelah dilakukan pengorganisasian baik intern Polri maupun bersama-sama dengan instansi terkait, lembaga Pilkada dan potensi masyarakat antara lain :kegiatan mewujudkan situasi kampanye yang kondusif, kegiatan pembuatan kesepakatan antar partai politik peserta pilkada, kegiatan pembentukan kekuatan gabungan, kegiatan penangkalan (pre-emptif), kegiatan pencegahan (preventif) dan kegiatan penegakan hukum (represif).